Social skills and sports: Pupils of an elite school of sports are more competitive and cooperative - Haas, A.; Wäsche, H.; Wittelsberger, R.; Nieken, P.; Woll, A. (German Journal of Exercise and Sport Research, 2023)
It is frequently observed that individuals who actively practice sports also do well in other domains of life, e.g., the labor market. While the underlying mechanisms are not yet fully understood, it is often argued that sports participation is embedded in a setting which fosters qualities which prove advantageous beyond sports. In the present paper, we examine competitive and cooperative behavior in children aged 10-13 years. Rather than on individual levels of sports participation, the focus is on the institutional setting of an elite school of sports (ESS) as compared to regular upper secondary schools. To obtain measures for competitiveness and cooperativeness, we utilize experimental methods which are established in economics. Our results show that ESS students are both more competitive and more cooperative than their counterparts at regular schools.